Prediction of Material Volume of Slope Failure in Nickel Surface Mine Using Limit Equilibrium Method 3D - Masagus Ahmad Azizi; Razak Karim; Irfan Marwanza; Muhammad Kemal Ghifari (Indonesian Mining Professionals Journal, 2019)
PT X had an accident  of slope failure that caused fatalities and injuries experienced by labor mining, and also some heavy mining equipments  buried  by  materials  that causing companies got financial loss. therefore important to analyze the slope stability of surface mining operation, and predicting total volume of slope failure to anticipate the impact of fatalities/ injuries and financial risks. This research  aim is  to analyze  slope stability before failure conditions, predicting volume of slope failure, and determine position of critical zone using limit equilibrium “Simpilfied Bishop” method 3-dimensional, then doing validation with calculation of actual volume by comparing results of topography maps before and after failure using the cut and fill method. From the result of research, the slope on unstability conditions, actual and predicted volume of  slope failure is  8,629 m3 and 10,559 m3, so percent of calculation error is 18.3% .